Water footprint in Hungary - Neubauer, Eva (Applied Studies in Agribusiness and Commerce, 2012)
More and more news report on water-related extreme environmental phenomena. Some of these are natural, which are often beyond the human race. But others are definitely due to anthropogenic effects. I think the water footprint index is able to highlight national and international water-use processes and gives us the opportunity of organizing a sustainable, consumer-, environmental- and governancefriendly management. 81% of the fresh water withdrawal is from surface water bodies in the EU. In Europe as a whole, 44% of abstraction is used for energy production, 24% for agriculture, 21% for public water supply and 11% for industry. Public water supply is confined to ground waters. To the water resources related human activity caused qualitative and quantitative amortisation will grow worse in the foreseeable future due to the climate change. Beside seasonal differences the sectoral differences are increasingly becoming critical between different areas, such as Southern and Western Europe. The former, wrong agricultural support system has worsened the situation since it gave financial aid for the used improper techniques of water-intensive crop cultivation. By today, this seems to be solved. Public water abstraction is affected by many factors, of which mostly are based on social situation and habits, but technological leakage receives a big role as well. Interesting, that for example the residents’water consumption in Eastern Europe decreased because price were raised and regular measurements were introduced. But in Southern Europe it increased due to tourism in the past period. Industrial water withdrawal decreased across Europe because of the decline of industry and the development of technologies. According to the European Environment Agency (EEA), the Union needs a sustainable, demand-driven leadership which focuses on the preservation and use efficiency. This have already appeared in politics and legal administration as well. Current research calls the attention to the significance and difficulties of this kind of domestic estimation presented trough the water footprint calculation of bread and pork in Hungary. The received data indicate the domestic water consumption trends in a modern approach. There is no doubt for me about the urgent necessity of water footprint calculation because as a result innovative, sustainability supported environmental, social, economical, and political relationships can be created – not just on local, regional or national level, but on interregional, European and even global stage.